Opportunities and Challenges for Utilizing the Social Potential of Infrastructure toward A Blue Economy - Habibie, Mulia; Masfar, Febi Hendra; Sidabutar, Yuanita FD; Amelia, Cevy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Since it first became popular around 2008, the blue economy has become an interesting topic in recent years. This principle is the future of water and sea-based economic governance. Geographically, Sijantung Village is located at 0°45'10.7"N 104°12'17.3"E and is one of the villages/sub-districts of Galang District, Batam City Government, Riau Islands Province. Sijantung Village consists of 12 islands. The area of Sijantung Village is approximately 39 .62 Km². With the potential for social infrastructure and historical tourism potential (heritage), Sijantung Village deserves to be the center of attention of the Batam City Government in developing the Blue Economy, as an integral part of the Central Government as a city that has a vision and mission to create a civilized, modern and prosperous society. The Blue Economy concept is very appropriate to be developed in Sijantung Subdistrict to answer the challenges of local and global economic systems which tend to be exploitative and damage the environment due to excessive exploitation of natural carrying capacity. The Blue Economy is sustainable development and is a correction and enrichment of the Green Economy with the motto "Blue Sky - Blue Ocean" where the economy grows, society prospers, nature is protected, and the sky and sea remain blue.